Reframing Duggan-Cronin: examining the recent emergence of Alfred Martin Duggan-Cronin's photographs in art exhibitions - Bangham, Rosemary (African Studies, 2024)
This study is about the photographs of Alfred Martin Duggan-Cronin. It is particularly concerned with the recent use of Duggan-Cronin's photographs in public exhibitions, especially art exhibitions. It suggests that the majority of these recent exhibitions favour an understanding of the photographs as art objects in opposition to how they were previously presented, in Duggan- Cronin's own time, as anthropological reference points. It also explores possible reasons for this apparent shift, as well as possible reasons for the re-emergence of the photographs in the first place. In particular the study engages with the subjects of photography, curation, archives, colonialism and anthropology.